First report of Fusarium weifangense, F. puerense and F. asiaticum causing leaf spot disease on Morus alba L. in China - Mei Lei; Rong Xiao; Lixia Zhang; Yu Tian; Zhongrong Zheng; Zehui Zhao; Tingting Zhao; Zhu Li; Haixia Ding (Crop Protection, 2026)

Flexural behavior and crack resistance of joints in hot-rolled section steel-UHPC composite deck under negative bending: Experiments and analysis - Wenyong Cai; Xudong Shao; Junhui Cao; Yang Wen; Rong Chen; Taowei Wang; Lin Peng; Lei Yu (Engineering Structures, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

Epinephelus coioides lnc32039 promotes the infection of iridovirus SGIV via inhibiting immune response and apoptosis - Yin-Mei Lan; Wen-Feng Yang; Yu-Qin Ma; Yu-Rong Lei; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2026)

A GPC3 antigenic peptide based nanovaccine to potentiate immunotherapy of hepatocellular carcinoma - Yang Qin; Longtianyang Lei; Chaoyi Liu; Chonghao Liao; Zhenghao Tao; Yao Cheng; Qing Gao; Runshu Fu; Zhuoyi Rong; Haitao Zhang; Hua Wei; Cui-Yun Yu (Chemical Engineering Journal, 2026)

Construction and application of an antifouling transistor-based cytosensor for detection of CTCs - Rong Zou; Huiling Yan; Lei Wang; Yu Chen; Caiyuan Liao; Bowen Zhang; Gang Chang; Ping Wang; Hanping He (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Optimizing lipid retention for anaerobic membrane bioreactors treating food waste: Balancing methane enhancement and membrane fouling control - Luwei Yan; Shuangquan Zhao; Yu Xi; Yaqian Liu; Yuxin Xiao; Zhen Lei; Qian Li; Rong Chen (Bioresource Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A Serpine1-F2-PAR1 axis facilitates apoptosis and disease severity during GCRV infection in grass carp - Yangyang Li; Liangming Chen; Bin Gui; Changchun Yu; Jinyan Lei; Yuxuan Shao; Haiping Liu; Zuoyan Zhu; Yaping Wang; Rong Huang (Fish & Shellfish Immunology, 2026)

Significant suppression of sulfur–containing organic aerosols by emission controls during the Hangzhou Asian Games - Jintian Zhang; Lei Liu; Jianxiong Rong; Lin Du; Zechen Yu; Shanshan Tang (Journal of Environmental Sciences, 2026)

Reduced graphene oxide enhances emerging contaminants removal in anaerobic wastewater treatment: Synergistic role of adsorption and microbial metabolism - Lianxu Wang; Zixin Zhang; Youfei Zhou; Zhen Lei; Yuan Yang; Yu-You Li; Rong Chen (Bioresource Technology, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Synergistic effects of climate forcings from three oceans on the reserve of “Atmospheric water tower” over the Tibetan Plateau - Pengjie Ren; Wusheng Yu; Stephen Lewis; Yaoming Ma; Yuanyuan Dang; Lei Zhong; Zhuanxia Zhang; Yong Liu; Lun Luo; Zhaowei Jing; Jingyi Zhang; Rong Guo; et al. (Journal of Hydrology, 2026)

Click chemistry-assisted hapten modification for enhanced immunoassay development: A promising strategy for clodinafop-propargyl detection in environmental and food samples - Yu Guo; Zhuanxu Xiang; Xinyue Ma; Rong Chen; Mei Dang; Xiaojun Jin; Anqi Chen; Ruyi Zeng; Lei Ke; Fanfan Yang (Food Chemistry, 2026)

Transforming Camellia oleifera meal into feedstuff: Enhancing value through detoxification and fermentation - Yiyan Cui; Yuheng Lei; Zhenming Li; Zhichang Liu; Min Song; Dun Deng; Zhimei Tian; Ting Rong; Pan Yang; Xianyong Ma; Miao Yu (Bioresource Technology, 2026)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Dietary prebiotics combined with iron supplementation: A two-pronged approach to reduce rice cadmium bioavailability - Rong-Yue Xue; Yao-Sheng Zhang; Jin-Feng Xi; Lei Zhou; Xin-Ying Lin; Tian-Wen Ye; Yu-Hang Bao; Dongmei Zhou; Hong-Bo Li (Food and Chemical Toxicology, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Specnuezhenide mitigates tunicamycin-induced liver injury in mice via ER stress modulation and metabolic reprogramming - Tianle Zhang; Dan Bi; Jiahui Li; Xin Jin; Huijuan Wu; Changyuan Yang; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Molecular Biology Reports, 2025)

The crucial role of immune factors in susceptibility to SARS-CoV-2 infection and severity of COVID-19 - Xing-Hao Yu; Rong-Rong Cao; Yi-Qun Yang; Han-Wen Cao; Fei-Yan Deng; Shu-Feng Lei (Molecular Genetics and Genomics, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Gut microbiota-metabolite dynamics in Sebastes schlegelii following Vibrio harveyi infection - Yindong Gu; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Zhiqi Zhang; Xiaojun Rong; Meijie Liao; Lei Qin; Bin Li; Zheng Zhang (Aquaculture International, 2025)

Research on quantitative monitoring of new meteorological-agricultural compound drought characteristics - Yang Yu; Lei Zhou; Wenliang Wang; Rong Tian; Jingxin Zhang; Senmiao Hu; Qingzhu Zhang; Yalan Li (Theoretical and Applied Climatology, 2025)

Loperamide-induced constipation is associated with excessive accumulation of bile acids and cholesterol in the liver of mice; attenuation by hesperidin - Jiahui Li; Dan Bi; Ya Nie; Huijuan Wu; Yuting Lei; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Food and Chemical Toxicology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Novel lineages of fungicolous Cordieritidaceae (Helotiales, Leotiomycetes) from southwest China - Feng-Ming Yu; Kandawatte Wedaralalage Thilini Chethana; Cui-Jin-Yi Li; Lei Lei; Jin-Rong Lu; Yi-Yun Guo; Qin-Yun Yang; Vinodhini Thiyagaraja; Qi Zhao (Mycological Progress, 2025)

Insights into soil microbial assemblages and nitrogen cycling function responses to conventional and biodegradable microplastics - Lili Rong; Yu Wang; Peter Meidl; Mujtaba Baqar; Andi Li; Lei Wang; Hongwen Sun (Journal of Hazardous Materials, 2025)

Deciphering biochar-driven membrane fouling mitigation mechanisms in high-solids AnMBRs: A multi-perspective analysis using computational fluid dynamics and interface thermodynamics - Chengfan Jiao; Shaowen You; Zhen Lei; Feixiang Zan; Qian Li; Yu-You Li; Rong Chen (Chemical Engineering Journal, 2025)

Semi-Supervised Maritime Object Detection: A Data-Centric Perspective - Meng Wu; Weilong Zhang; Rong Min; Lei Zhang; Yueting Xu; Yuheng Qin; Jing Yu (Journal of Marine Science and Engineering, 2025)
Semi-supervised object detection (SSOD) has emerged as a promising technique to boost the performance of the detectors, utilizing both labeled and unlabeled data. However, in marine environments, SSOD faces formidable challenges posed by complex conditions like shore-based landscapes, varying ship scales, and diverse weather, which complicate data acquisition and thus the generation of accurate pseudo-labels. To tackle these issues, we propose two novel strategies, depth-aware pseudo-label filtering (DAPF) and dynamic region mixup (DRMix) augmentation, from a data-centric perspective. Specifically, the DAPF strategy incorporates depth information as a prior to refine pseudo-labels by filtering out unreliable ones, thereby improving the quality of pseudo-label–data pairs used for training. Meanwhile, DRMix augmentation dynamically mixes images at the regional level, generating diverse and representative data suitable for maritime object detection tasks. Extensive experiments on maritime datasets validate the effectiveness of our approach, achieving mAP improvements of 2.2% on the SeaShips dataset and 0.9% on the Singapore Maritime dataset compared to other state-of-the-art (SOTA) methods. Our code will be made publicly available.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Transcutaneous Auricular Vagus Stimulation Attenuates LPS-Induced Depression-Like Behavior by Regulating Central α7nAChR/JAK2 Signaling - Junying Wang; Yu Wang; Yu Chen; Jinling Zhang; Yue Zhang; Shaoyuan Li; Haohan Zhu; Xingke Song; Liwei Hou; Lei Wang; Yifei Wang; Zixuan Zhang; et al. (Molecular Neurobiology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Partial organic substitution increases soil quality and crop yields but promotes global warming potential in a wheat-maize rotation system in China - Gong Wu; Hai-meng Huang; Bei-bei Jia; Lei-lei Hu; Chong-sheng Luan; Qi Wu; Xiao-yu Wang; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Soil and Tillage Research, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Synergic treatment of domestic wastewater and food waste in an anaerobic membrane bioreactor demo plant: Process performance, energy consumption, and greenhouse gas emissions - Zhen Lei; Jiale Zheng; Jiale Liu; Qian Li; Jingjing Xue; Yuan Yang; Zhe Kong; Yu-You Li; Rong Chen (Water Research, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Numerical simulation and experimental verification of solar PVT coupled PEM electrolyzer system for hydrogen production - Yixuan Ma; Mingzhi Zhao; Feng Bai; Rong Yu; Lei Liu; Jianan Wang (Fuel, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

A study on the cyclic shear and particle breakage characteristics of the interface between steel and calcareous sand - Rui Wang; Jukun Guo; Shengyou Lei; Xiaowei Wang; Wentao Rong; Zhihua Yu (Marine Georesources & Geotechnology, 2023)

Review of silicon recovery in the photovoltaic industry - Yuelong Yu; Xinjie Bai; Shaoyuan Li; Jianghao Shi; Lei Wang; Fengshuo Xi; Wenhui Ma; Rong Deng (Current Opinion in Green and Sustainable Chemistry, 2023)

Associations of exposure to bisphenol A and its substitutes with neurodevelopmental outcomes among infants at 12 months of age: A cross-sectional study - Zhuanning Xia; Cheng Lv; Yan Zhang; Rong Shi; Qi Lu; Ying Tian; Xiaoning Lei; Yu Gao (Chemosphere, 2023)

Properly interpret metabolic inhibition results to identify primary mercury methylating microbes - Pei Lei; Ri-Qing Yu; Yaqi Kong; Stefan Bertilsson; Martin Tsz-Ki Tsui; Tao Jiang; Jiating Zhao; Yu-Rong Liu; Rinklebe Jörg; Huan Zhong (Critical Reviews in Environmental Science and Technology, 2023)

Sludge granulation in PN/A enhances nitrogen removal from mainstream anaerobically pretreated wastewater - Zhen Lei; Jingjing Xue; Yongning Feng; Yu-You Li; Zhe Kong; Rong Chen (Science of The Total Environment, 2023)

In-situ constructing amidoxime groups on metal-free g-C3N4 to enhance chemisorption, light absorption, and carrier separation for efficient photo-assisted uranium(VI) extraction - Kaifu Yu; Yi Li; Xin Cao; Ruixiang Wang; Li Zhou; Linzhen Wu; Ningning He; Jia Lei; Dengjiang Fu; Tao Chen; Rong He; Wenkun Zhu (Journal of Hazardous Materials, 2023)

Balanced phosphorus fertilization enhances soil bacterial network complexity to maintain multifunctionality and plant production in dryland agricultural systems - Lei Liu; Rong Yan; Li Zhu; Yu Yang; Zhiyuan Gao; Wenjie Yang; Jinshan Liu (Agriculture, Ecosystems & Environment, 2023)

3,5,6-Trichloro-2-pyridinol confirms ototoxicity in mouse cochlear organotypic cultures and induces cytotoxicity in HEI-OC1 cells - Mao Huang; Mingshan Zou; Shuangshuang Mao; Wenqi Xu; Yu Hong; Haiyan Wang; Fei Gui; Lei Yang; Fuzhi Lian; Rong Chen (Toxicology and Applied Pharmacology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The acceleration on decolorization of azo dyes by magnetic lignin-based materials via enhancing the extracellular electron transfer - Rong-ping Chen; Xin-yuan Wei; Cheng-hao Gan; Bing-cai Cai; Wen-jie Xu; Shareen Niyazi; Quan Wang; Lei Yu; Hui-hua Min; Qiang Yong (Journal of Environmental Management, 2023)

Progress and perspective in enrichment and separation of radionuclide uranium by biomass functional materials - Jia Lei; Huanhuan Liu; Li Zhou; Yazhou Wang; Kaifu Yu; Hui Zhu; Bo Wang; Mengxuan Zang; Jian Zhou; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Performance evaluation of a novel relay parallel push-pull ventilation system for long-distance pollution control - Yu Zhou; Wan-Rong Ren; Zhiyuan Li; Yuxin Fang; Lei Jia; Yi Wang (Building and Environment, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Climatic seasonality challenges the stability of microbial‐driven deep soil carbon accumulation across China - Shuhai Wen; Jiaying Chen; Ziming Yang; Lei Deng; Jiao Feng; Wen Zhang; Xiao‐Min Zeng; Qiaoyun Huang; Manuel Delgado‐Baquerizo; Yu‐Rong Liu (Global Change Biology, 2023)
Microbial residues contribute to the long‐term stabilization of carbon in the entire soil profile, helping to regulate the climate of the planet; however, how sensitive these residues are to climatic seasonality remains virtually unknown, especially for deep soils across environmental gradients. Here, we investigated the changes of microbial residues along soil profiles (0–100 cm) from 44 typical ecosystems with a wide range of climates (~3100 km transects across China). Our results showed that microbial residues account for a larger portion of soil carbon in deeper (60–100 cm) vs. shallower (0–30 and 30–60 cm) soils. Moreover, we find that climate especially challenges the accumulation of microbial residues in deep soils, while soil properties and climate share their roles in controlling the residue accumulation in surface soils. Climatic seasonality, including positive correlations with summer precipitation and maximum monthly precipitation, as well as negative correlations with temperature annual range, are important factors explaining microbial residue accumulation in deep soils across China. In particular, summer precipitation is the key regulator of microbial‐driven carbon stability in deep soils, which has 37.2% of relative independent effects on deep‐soil microbial residue accumulation. Our work provides novel insights into the importance of climatic seasonality in driving the stabilization of microbial residues in deep soils, challenging the idea that deep soils as long‐term carbon reservoirs can buffer climate change.

Characteristics and comparisons of the aerobic and anaerobic denitrification of a Klebsiella oxytoca strain: Performance, electron transfer pathway, and mechanism - Cheng-jia Ju; Shareen Niyazi; Wen-yin Cao; Quan Wang; Rong-ping Chen; Lei Yu (Journal of Environmental Management, 2023)

Constructing electron transport channels in FeSe2 microspheres by a facile strategy for superior long-life and ultrafast sodium-ion storage - Ming Xu; Yu Ma; Rong Liu; Huanhao Xiao; Liming Chen; Ziqiang Zhang; Lei Wang; Guohui Yuan (Chemical Engineering Journal, 2023)

Urinary neonicotinoid insecticides and adiposity measures among 7-year-old children in northern China: A cross-sectional study - Zhenping Lu; Yi Hu; Lap Ah Tse; Jinxia Yu; Zhuanning Xia; Xiaoning Lei; Yan Zhang; Rong Shi; Ying Tian; Yu Gao (International Journal of Hygiene and Environmental Health, 2023)

Responses of Bacillus sp. under Cu(II) stress in relation to extracellular polymeric substances and functional gene expression level - Ling-ling Wang; Zheng-yan Yin; Yun Xu; Miao-yu Deng; Kai-ming Zhang; Quan Wang; Rong-ping Chen; Lei Yu (Environmental Science and Pollution Research, 2023)

Corrigendum to ’ Biochar enhances the biotransformation of organic micropollutants (OMPs) in an anaerobic membrane bioreactor treating sewage’ [Water Research 223 (2022) 118974] - Zhen Lei; Shixin Zhang; Lianxu Wang; Qian Li; Yu-You Li; Xiaochang C. Wang; Rong Chen (Water Research, 2023)

Abundant bacterial subcommunity is structured by a stochastic process in an agricultural system with P fertilizer inputs - Lei Liu; Li Zhu; Rong Yan; Yu Yang; Jonathan M. Adams; Jinshan Liu (Science of The Total Environment, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Efficient inactivation of the contamination with pathogenic microorganisms by a combination of water spray and plasma-activated air - Li Guo; Pengyu Zhao; Yikang Jia; Tianhui Li; Lingling Huang; Zifeng Wang; Dingxin Liu; Zhanwu Hou; Yizhen Zhao; Lei Zhang; Hua Li; Yu Kong; et al. (Journal of Hazardous Materials, 2023)

A study on the correlation between intrauterine microbiota and uterine pyogenesis in dogs - Hui-Hua Zheng; Chong-Tao Du; Yu-Zhu Zhang; Chao Yu; Rong-Lei Huang; Xin-Yue Tang; Guang-Hong Xie (Theriogenology, 2023)

Trophoblast Stem-Cell-Derived Exosomes Alleviate Cardiotoxicity of Doxorubicin via Improving Mfn2-Mediated Mitochondrial Fusion - Junfeng Duan; Xiaoli Liu; Song Shen; Xi Tan; Yi Wang; Lian Wang; Lina Kang; Kun Wang; Zhonghai Wei; Yu Qi; Lei Hu; Biao Xu; et al. (Cardiovascular Toxicology, 2023)
Doxorubicin (Dox) is an anticancer drug widely used in tumor chemotherapy, but it has the side-effect of cardiotoxicity, which is closely related to mitochondrial damage. Mitochondrial dynamics is a quality control mechanism that usually helps to maintain a healthy mitochondrial pool. Trophoblast stem cell-derived exosomes (TSC-Exos) have been shown to protect cardiomyocytes from DOX-induced cardiotoxicity. To explore whether the cardioprotective role is mediated by the regulation of mitochondrial dynamic mechanism, TSC-Exos were isolated from human trophoblast stem cells by ultracentrifugation and characterized by Western blot and transmission electron microscopy. Cellular experiments of H9c2 cardiomyocytes co-cultured with Dox and TSC-Exos were performed in vitro to determine the levels of reactive oxygen species generation and apoptosis level. An animal model of heart failure was established by intraperitoneal injection of Dox in vivo, therapy mice were received additional intracardiac injection of TSC-Exos, then, the cardiac function, cardiomyocyte apoptosis and mitochondrial fragmentation were ameliorated. Histology assays suggest that Dox caused an increased tendency of mitochondrial fission, which was manifested by a decrease in the average size of mitochondria. By receiving TSC-Exos treatment, this effect was eliminated. In summary, these results suggest that TSC-Exos alleviate DOX-induced cardiotoxicity through antiapoptotic effect and improving mitochondrial fusion with an increase in Mfn2 expression. This study is the first to provide a potential new treatment scheme for the treatment of heart failure from the perspective of the relationship between TSC-Exos and mitochondrial dynamics.

Expression of RUNX2/LAPTM5 in the Induction of MC3T3-e1 Mineralization and Its Possible Relationship with Autophagy - Lei Xing; Yanqin Li; Wenhao Li; Rong Liu; Yuanming Geng; Weiqun Ma; Yu Qiao; Jianwen Li; Yingtao Lv; Ying Fang; Pingping Xu (Tissue Engineering and Regenerative Medicine, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Reconstruction method of irregular seismic data with adaptive thresholds based on different sparse transform bases - Hu Zhao; Tun Yang; Yu-Dong Ni; Xing-Gang Liu; Yin-Po Xu; Yi-Lei Zhang; Guang-Rong Zhang (Applied Geophysics, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Chlamydia trachomatis induces autophagy by p62 in HeLa cell - Fuyan Wang; Hongbo Zhang; Xiaofang Lu; Quan Zhu; Tingting Shi; Rong Lu; Ping Yu; Lei Zhang; Yong Wang (World Journal of Microbiology and Biotechnology, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Chinese public participation monitoring and warning system for geological hazards - Sheng-nan Wu; Yu Lei; Peng Cui; Rong Chen; Pi-hua Yin (Journal of Mountain Science, 2020)

Atorvastatin ameliorates depressive behaviors and neuroinflammatory in streptozotocin-induced diabetic mice - Zhang Hai-Na; Yu Xu-Ben; Tang Cong-Rong; Cao Yan-Cheng; Yang Fan; Xu Lei-Mei; Sun Ruo-Lan; Ye-Zi; Wang Ye-Xuan; Liang Jing (Psychopharmacology, 2020)

Comparative profiling of roots small RNA expression and corresponding gene ontology and pathway analyses for low- and high-cadmium–accumulating genotypes of wheat in response to cadmium stress - Min Zhou; Shigang Zheng; Yunfang Li; Rong Liu; Lei Zhang; Yu Wu (Functional & Integrative Genomics, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Characterization and diagnostic marker development for Yr28-rga1 conferring stripe rust resistance in wheat - Shigang Zheng; Yu Wu; Min Zhou; Lian Zeng; Rong Liu; Yunfang Li; Zehou Liu; Chihong Zhang; Lu Lu; Lei Zhang (European Journal of Plant Pathology, 2020)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

Comparative analysis of root transcriptome profiles between low- and high-cadmium-accumulating genotypes of wheat in response to cadmium stress - Min Zhou; Shigang Zheng; Rong Liu; Jing Lu; Lu Lu; Chihong Zhang; Zehou Liu; Congpei Luo; Lei Zhang; Yu Wu (Functional & Integrative Genomics, 2019)

Benzene metabolite 1,2,4-benzenetriol changes DNA methylation and histone acetylation of erythroid-specific genes in K562 cells - Chun-Hong Yu; Yang Li; Xiao Zhao; Shui-Qing Yang; Lei Li; Ning-Xuan Cui; Long Rong; Zong-Chun Yi (Archives of Toxicology, 2019)

Effective inhibition of different Japanese encephalitis virus genotypes by RNA interference targeting two conserved viral gene sequences in vitro and in vivo - Lei Yuan; Xiaojuan Feng; Xuelian Gao; Yu Luo; Chaoyue Liu; Peng Liu; Guolin Yang; Hong Ren; Rong Huang; Yalan Feng; Jian Yang (Virus Genes, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

EZH2 promotes cell proliferation by regulating the expression of RUNX3 in laryngeal carcinoma - Rong Lian; Huimin Ma; Zhiyan Wu; Guozheng Zhang; Lei Jiao; Wenjie Miao; Qianqian Jin; Ruixue Li; Ping Chen; Haixu Shi; Wenfa Yu (Molecular and Cellular Biochemistry, 2018)

Cyclooxygenase-2 (COX-2) polymorphism rs689466 may contribute to the increased susceptibility to post-traumatic osteomyelitis in Chinese population - Lei Wang; Nan Jiang; Qing-rong Lin; Cheng-he Qin; Yan-jun Hu; Bin Yu (Infectious Diseases, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Possible Effects of Electric Fields on a Pair of Spherical Cells - Yu Zheng; Jing Xue; Yang Gao; Lei Dong; Jun-rong Dou; Wei Ma (The Journal of Membrane Biology, 2017)

Glucocorticoid-Potentiated Spinal Microglia Activation Contributes to Preoperative Anxiety-Induced Postoperative Hyperalgesia - Rao Sun; Zhibin Zhao; Jiying Feng; Jinhua Bo; Hui Rong; Yishan Lei; Cui’e Lu; Xiaobao Zhang; Bailing Hou; Yu’e Sun; Yue Liu; Zhengliang Ma; et al. (Molecular Neurobiology, 2017)

The levels of DNGR-1 and its ligand-bearing cells were altered after human and simian immunodeficiency virus infection - Wen-Rong Yao; Dong Li; Lei Yu; Feng-Jie Wang; Hui Xing; Gui-Bo Yang (Immunologic Research, 2017)

CDK inhibitor SU9516 induces tetraploid blastocyst formation from parthenogenetically activated porcine embryos - Qing Guo; Long Jin; Hai-Ying Zhu; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Guang-Lei Zhang; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Jin-Dan Kang; et al. (Biotechnology Letters, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Evaluating the contribution of Yr genes to stripe rust resistance breeding through marker-assisted detection in wheat - Shigang Zheng; Yunfang Li; Lu Lu; Zehou Liu; Chihong Zhang; Donghui Ao; Lirong Li; Chunyan Zhang; Rong Liu; Congpei Luo; Yu Wu; Lei Zhang (Euphytica, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Selenium and Iodine Levels in Subjects with Kashin-Beck Disease: a Meta-analysis - Lei Yang; Guang-hui Zhao; Fang-fang Yu; Rong-qiang Zhang; Xiong Guo (Biological Trace Element Research, 2016)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Selenium geochemical distribution in the environment and predicted human daily dietary intake in northeastern Qinghai, China - Dasong Yu; Dongli Liang; Lingming Lei; Rong Zhang; Xiaofeng Sun; Zhiqing Lin (Environmental Science and Pollution Research, 2015)

Failure modes of reinforced concrete columns of buildings under debris flow impact - Chao Zeng; Peng Cui; Zhiman Su; Yu Lei; Rong Chen (Landslides, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Esthetic Management of Mucogingival Defects After Excision of Epulis Using Laterally Positioned Flaps - Yu-feng Xie; Rong Shu; Jie-lei Qian; Zhi-kai Lin; Georgios E. Romanos (Cell Biochemistry and Biophysics, 2015)

The impact of the cognition of landscape experience on tourist environmental conservation behaviors - Yu-ling Zhang; Jie Zhang; Hong-Lei Zhang; Shao-wen Cheng; Yong-rui Guo; Jin-hai Ma; Jing-rong Sun (Journal of Mountain Science, 2015)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Interactions between CYP1A1 polymorphisms and cigarette smoking are associated with the risk of hepatocellular carcinoma: evidence from epidemiological studies - Lei Yu; Lei Sun; Yang-Fang Jiang; Bao-Ling Lu; De-Rong Sun; Li-Ying Zhu (Molecular Biology Reports, 2012)

Mitochondrial Permeability Transition Induced by Different Concentrations of Zinc - Xiao-Rong Liu; Jia-Han Li; Yue Zhang; Yu-Shu Ge; Fang-Fang Tian; Jie Dai; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2011)

Effects of Schisandra sphenanthera extract on the blood concentration of tacrolimus in renal transplant recipients - Hua-Wen Xin; Qing Li; Xiao-Chun Wu; Yan He; Ai-Rong Yu; Lei Xiong; Ying Xiong (European Journal of Clinical Pharmacology, 2011)

LysGH15B, the SH3b Domain of Staphylococcal Phage Endolysin LysGH15, Retains High Affinity to Staphylococci - Jingmin Gu; Rong Lu; Xiaohe Liu; Wenyu Han; Liancheng Lei; Yu Gao; Honglei Zhao; Yue Li; Yuwen Diao (Current Microbiology, 2011)

Biophysical Studies on the Interactions of a Classic Mitochondrial Uncoupler with Bovine Serum Albumin by Spectroscopic, Isothermal Titration Calorimetric and Molecular Modeling Methods - Yue Zhang; Jia-Han Li; Yu-Shu Ge; Xiao-Rong Liu; Feng-Lei Jiang; Yi Liu (Journal of Fluorescence, 2011)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wen-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Relationships between thiopurine S-methyltransferase polymorphism and azathioprine-related adverse drug reactions in Chinese renal transplant recipients - Hua-Wen Xin; Hui Xiong; Xiao-Chun Wu; Qing Li; Lei Xiong; Ai-Rong Yu (European Journal of Clinical Pharmacology, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wun-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Molecular cloning, characterization and expression of two rapeseed (Brassica napus L.) cDNAs orthologous to Arabidopsis thaliana phenylalanine ammonia-lyase 1 - Yu Ni; Hong-Lin Jiang; Bo Lei; Jia-Na Li; You-Rong Chai (Euphytica, 2008)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Pharmacodynamics and Toxicodynamics of Drug Action: Signaling in Cell Survival and Cell Death - Ah-Ng Tony Kong; Sandhya Mandlekar; Rong Yu; Wei Lei; Adedigbo Fasanmande (Pharmaceutical Research, 1999)